(untitled) - Arny, Thomas T. (Boston, 2004)
Now one of the best selling Astronomy textbooks is available in a "stars-first" organization. The same great writing style, the same great pedagogical tools helping students through concepts as well as the same complete technology package is available (CD-ROM, Website, PowerWeb and NetTutor)!
Keywords: Astronomy,Thiên văn học